Advances in Automatic Hexahedral Meshing. (September 2020) - Li, Chentao; Qiang, Sheng; Hua, Xia
Abstract: The problem of Automated hexahedral meshing has been a puzzle of mesh generation research for years. A great deal of effort has been made on how to generate high-quality hexahedral mesh automatically. The conflicts between different requirements of the mesh provide the challenge. The paper systematically reviews the requirements of the hexahedral meshing challenge, sums up the various approaches to solve the problem and their respective characteristics, analyzes the breakthroughs in recent research, especially in multi-subdomain and strebel differential method. It finally points out that the development of geometric aspects and optimal transmission theory will be the main topics for the research on the organizational creativity in the future.